Antibodies: what makes us stronger - Natalia T. Freund (Taylor & Francis Group, 2021)
Neutralizing antibodies are the basis of almost all approved prophylactic vaccines and the foundation of effective protection from pathogens, including the recently emerging SARS Coronavirus 2 (SARS-CoV-2). However, the contribution of antibodies to protection and to the course of the disease during first-time exposure to a pathogen is unknown. We analyzed the antibodies and B cell responses in severe and mild COVID-19 patients. Despite our primary assumption that high antibody titers contribute to a mild disease, we found that severe COVID-19 illness, and not mild infection, correlates with strong anti-viral antibody and memory B cell responses. This phenomenon was also demonstrated for anti-Mycobacterium tuberculosis inhibiting antibodies that we recently isolated from an actively infected Tuberculosis-sick donor. This correlation between disease severity and antibody responses can be explained by the fact that high viral loads drive B cell stimulation and generation of high-affinity antibodies that will be protective upon future encounter with the particular pathogen.